EVALUATION OF DEFOLIANTS TO FACILITATE MECHANICAL PICKING IN RAINFED COTTON - K , ASHOK KUMAR (The Journal of Research ANGRAU, 2026)
A field experiment was conducted during the kharif season of 2024 at Regional AgriculturalResearch Station, Nandyal to evaluate the effect of defoliants on facilitating mechanical pickingin cotton.The treatments consisted of T1:Control, T2:Ethrel@3000ppm,T3:Thidiazuron@500ppm,T4:Sodiumchlorate@0.9%, T5:CICRDefoliant, T6:Hydrogencyanamide @5000ppm, T7:T2+5%ofurea,T8:T2+Diuron@400 ppm, T9:T2+Sodiumchlorate @0.9% and T10:T3+Diuron@400ppm. Higherpercent defoliation (95.5) at 10 days after spraying was recorded with T3 (Thidiazuron @500ppm) and was on par withT10 (93.1) followed byT9(89.5), T5(86.2) and lower percent defoliation(5.3) was recorded with T1(Control). Further, higher earliness index (75%) was recorded with T10(Thidiazuron@500ppm+Diuron @ 400ppm) and was on par T3 (72%) followed by T4 (65%);andlower earliness index(38)was recorded with T1 (Control). It can be concluded that higher defoliationwas attained with application of Thidiazuron @500 ppm+ Diuron @400ppm and also higher cottonseed yield. There was considerable correlation between defoliation at 5 DAS and 10 DAS. Further,the quality parameters were not significantly effected due to defoliants application.